TWITWAR DAN RASISME DI MEDIA SOSIAL: Wacana Cuitan Farhat Abbas vs Basuki Tjahaja Purnama di Kompas.com dan Merdeka.com - Caesarlita, Diandra Septa (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
This article is based on the presence of online media that allows people to get information easier. In the process of making news, the editorial in the online media should pay attention to speed and accuracy, particularly in the case of racism that is sensitive and must be maintained properly. As was the case on Farhat Abbas, a lawyer celebrity over statements through his Twitter account which offended the ethnicity of Basuki Tjahaja Purnama (Ahok), deputy governor of Jakarta. This article disclosures the discourse of racism in Kompas.com and Merdeka.com as well as describing the production process of the news about tweets war cases that occurred between Farhat Abbas and Basuki Tjahaja Purnama in both media. The framework that is used to achieve this goal is a discourse analysis of Norman Fairclough, supported by the concept of racism from George Fredrickson and George Ritzer. Using a qualitative approach through document search and interviewing method by comparing two perspectives and styles of online media, namely Kompas.com and Merdeka.com. Informants of this study were assistant managing news editor and coordinator of Kompas.com coverage from Merdeka.com. The main findings of this study indicate that the news from both online media, although it does not contain racist discourse and nothing complaint from any party, the tweet war produced on Twitter has been commodified by the media to get public attention. To cite this article (7th APA style): Caesarlita, D. S. (2014). Twitwar dan Rasisme di Media Sosial: Wacana Cuitan Farhat Abbas vs Basuki Tjahaja Purnama di Kompas.com dan Merdeka.com [Tweets War and Racism in Social Media]. Journal Communication Spectrum, 4(2), 126-140.